INVESTIGATIONS OF REGULARITIES IN DISTRIBUTION OF TECTONIC STRESSES IN THE KURIL-KAMCHATKA ZONE - Timofei K. Zlobin; Anastasia Yu. Polets (Геодинамика и тектонофизика, 2015)
The article highlights the importance of researching earthquake which occurred in the Sakhalin and Kuril Islands in combination with studies of seismic dislocations and tectonic movements caused by such earthquakes. It is shown that seismic dislocations and tectonic movements can be studied from focal mechanisms of earthquakes. Data on the crustal structure and earthquake sources are valuable for finding solutions of fundamental problems of geotectonic and geodynamics; therefore, it is challenging to juxtapose such data while studying the transition zone from the Eurasian continent to the Pacific Ocean.The crustal structure and distribution of earthquake are considered along the Shantar-Matua profile which runs from the western border of the Tatarsky Strait (the Primorie coast) through South Sakhalin and the Okhotsk Sea up to the Matua Island. Based on the NEIC catalogue, a depth profile showing earthquake hypocenters is constructed for a zone which widths on both sides of the Shantar-Matua profile amounted to 200km. This allows us to consider specific features of the deep structure of the crust and positions of the earthquake sources in the crust and in the upper mantle along the uniform profile (Fig. 1, a, b).Data on catastrophic earthquakes with magnitudes of 8.3 and 8.1 that occurred on 15 November 2006 and 13 January 2007 in the region of the Simushir Island are collated with results of onshore and marine deep seismic researches by DSS, CMRW, MSWE, MEW methods in the region of the Middle Kurils. The structure of the crust and focal zones of these earthquakes are considered in conjunction (Figures 2–8).Cyclic changes in the state of stresses of the lithosphere and corresponding seismic dislocations in the focal zone of the catastrophic Shikotan earthquake of 04 October 1994 (M=8.1, depths 0-150km) are revealed (Table 1, Fig. 9).We apply the method of cataclastic analysis (MCA) of fractures to assess the state of stresses of the crust in the area of the Shikotan earthquake. This method is the basis for new experimental studies of the state of tectonic stresses and deformations and properties of rocks in their natural bedding. The method of reconstruction of tectonic stresses was designed by Yu.L. Rebetsky. Stresses are reconstructed from Centroid Moment Tensor data (СМТ), i.e. solutions for earthquakes recorded in NEIC catalogues (Figures 10–15). Based on reconstructed parameters of the recent state of stresses of the crust and the upper mantle of the Southern Kurils, there are grounds to conclude that spacious areas of stable stress tensor parameters are present in the region under studies, along with local sites wherein these parameters are subject to anomalously fast changes.